Parathyroid disorders : focusing on unmet needs - Brandi, Maria Luisa 1953- (Basel : Karger, 2019)
This book is devoted exclusively to hyper- and hypoparathyroidism with a focus on clinical practice guidelines explained by experts in the field. The clinical, genetic, biochemical, and pharmacological aspects of the most common parathyroid conditions are discussed comprehensively. The 15 chapters review the various forms of hyperparathyroidism and hypoparathyroidism and present data derived from widely diverse sources. New therapeutic approaches for chronic hypoparathyroidism continue to pique interest in parathyroid diseases and show that more research must be done to optimize care. The aim of this book is to serve as a practical guide to clinical management of common parathyroid conditions and to disseminate knowledge useful to the clinic, both for specialists and general practitioners. Also, under- and postgraduates, specialist nurses, and non-experts in the field will find this book to be a valuable source of current information.
Keywords: HIPERPARATIROIDISMO; HIPOPARATIROIDISMO